The Facets of primary and secondary school students’ wellbeing during the first wave of the COVID-19 pandemic: A qualitative analysis of Austrian and Italian educational policy - Francesconi , Denis; Gross, Barbara; Agostini, Evi (Psihološka istraživanja, 2021)
The coronavirus pandemic has revealed the limits of current social and educational structures. In most countries, COVID-19 has compromised the wellbeing of students and their families and teachers. During the first wave of the pandemic, school systems all over the world had to respond quickly and appropriately to the systemic shock. A variety of policy measures were put in place in different countries to tackle the extensive impact of the pandemic. This paper adopts a critical perspective as its theoretical framework and the UN Sustainable Development Goals (SDGs) as its policy framework, and aims to provide a qualitative analysis of selected educational policies deployed by Italy and Austria to support the wellbeing of school pupils. We undertook qualitative content analysis of educational policy documents in Italy and Austria from February to the end of August 2020 to answer the following research question: How have educational policies in Italy and Austria fostered students’ wellbeing during the first wave of the COVID-19 pandemic? The results show that the Italian and Austrian systems had different strategies and put different initiatives in place to support wellbeing. However, educational policies in both countries put a stronger focus on the individual physical wellbeing of students during the period under study, and tended to neglect social wellbeing, albeit to a greater extent in Italy. In its conclusion, the paper reflects on the opportunities offered by this emergency to school systems to position wellbeing (in the broader sense of eudaimonic wellbeing) at the center of educational policy.
Keywords: wellbeing; SDGs; school system; qualitative policy analysis; COVID-19